Measurement of brain activation during an upright stepping reaction task using functional near‐infrared spectroscopy. Issue 11 (19th November 2012) - Huppert, Theodore; Schmidt, Benjamin; Beluk, Nancy; Furman, Joseph; Sparto, Patrick
<x xml:space="preserve">Abstract</x> Functional near‐infrared spectroscopy (fNIRS) is a non‐invasive brain imaging technology that uses light to measure changes in cortical hemoglobin concentrations. FNIRS measurements are recorded through fiber optic cables, which allow the participant to wear the fNIRS sensors while standing upright. Thus, fNIRS technology is well suited to study cortical brain activity during upright balance, stepping, and gait tasks. In this study, fNIRS was used to measure changes in brain activation from the frontal, motor, and premotor brain regions during an upright step task that required subjects to step laterally in response to visual cues that required executive function control. We hypothesized that cognitive processing during complex stepping cues would elicit brain activation of the frontal cortex in areas involved in cognition. Our results show increased prefrontal activation associated with the processing of the stepping cues. Moreover, these results demonstrate the potential to use fNIRS to investigate cognitive processing during cognitively demanding balance and gait studies. Hum Brain Mapp 34:2817–2828, 2013. © 2012 Wiley Periodicals, Inc.